The beginning of a strategic alliance’ - Abdul Hamid, Hasidah (Faculty of Medicine, 2022)
On the 30th of November 2022, Professor Dr. Pemra C Unalan, a Professor of Primary Care from the Marmara University in Turkey visited the Department of Primary Care Medicine in Sungai Buloh Campus. During the visit, the department members headed by Associate Professor Dr. Siti Fatimah Badlishah Sham and Profesor Dr. Anis Safura Ramli welcomed Prof. Dr. Unalan as we get to know each other better. Associate Professor Dr. Noor Shafina Mohd Nor, Deputy Dean (Postgraduate & Professional Training) also extended a warm welcome by connecting virtually with Prof Unalan during her visit.